2008
DOI: 10.1161/hypertensionaha.108.115600
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Home Versus Clinic Blood Pressure With Antihypertensive Treatments

Abstract: Home blood pressure (HBP) monitoring is recommended for assessing the effects of antihypertensive treatment, but it is not clear how the treatment-induced changes in HBP compare with the changes in clinic BP (CBP). We searched PubMed using the terms “home or self-measured blood pressure,” and selected articles in which the changes in CBP and HBP (using the upper arm oscillometric method) induced by antihypertensive drugs were presented. We performed a systematic review of 30 articles published before March 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
2
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 51 publications
(147 reference statements)
1
25
2
2
Order By: Relevance
“…[28][29][30] This is in concordance with results from this study and might be caused, at least in part, by regression to the mean. 31 The fact that ABPM was not used to qualify patients for entry into the study means that some patients with ABPM levels in the nonhypertensive range were included (n=7; 15.9%).…”
Section: Discussionsupporting
confidence: 92%
“…[28][29][30] This is in concordance with results from this study and might be caused, at least in part, by regression to the mean. 31 The fact that ABPM was not used to qualify patients for entry into the study means that some patients with ABPM levels in the nonhypertensive range were included (n=7; 15.9%).…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, the findings showed that rumination outside the laboratory was associated with large increases in ambulatory SBP and DBP, 19 mm Hg and a 11 mm Hg, respectively, after statistical adjustments for age and BMI. This result is particularly intriguing if we consider the prognostic value of BP for the development of cardiovascular disease (Boggia et al, 2007), and that a 10 mm Hg change is the target to evaluate the efficacy of antihypertensive medications (Ishikawa, Carroll, Kuruvilla, Schwartz, & Pickering, 2008). We also showed a relationship between BP reactivity to the anger interview in the laboratory and ambulatory BP increases from nonrumination to rumination periods in daily life.…”
Section: Discussionmentioning
confidence: 80%
“…43,44 Indeed, a recent meta-analysis describing the changes in BP in subjects treated with antihypertensive medication or placebo has demonstrated the improved stability The equivalence of SBPM with ABPM N McGowan and PL Padfield of self-measurements, rather than clinical measurements. 45 There is also evidence that the use of SBPM can lead to improved compliance with antihypertensive medication 46 and improved BP control. 47,48 Although ABPM has been shown to be costeffective 9,10 in diagnosing hypertension, it is impractical for assessing and managing all patients in primary care.…”
Section: Discussionmentioning
confidence: 99%